GEOECOLOGICAL ANALYSIS OF LANDSCAPE ZONES OF TAVUSH REGION (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The article analyzes the geoecological condition of the landscape zones of Tavush Region. Anthropogenic load on natural landscapes expresses the degree of intensity of anthropogenic negative impacts in a given landscape zone. And anthropogenic impact on landscapes is expressed by the nature of land use structure. According to the concept of B. Kochurov, ecological and economic balance of the area 1–6 points of expert assessment are used to determine the degree of anthropogenic load on the area. Areas depending on the type of land use receive a corresponding score and are grouped into appropriate groups. Using B. Kochurov's methodology and applying the cartographic tools of the ArcGis, we obtained the map of the anthropogenic load of the landscape zones and calculated the surfaces of the areas with the corresponding level of load in each zone expressed as percentages. Then we carried out a spatial quantitative assessment of the anthropogenic load of the landscape zones with the absolute and relative coefficients of the selected concept and the tools of the ArcGis. As a result of the research, the forest-steppe zone was considered an area of critical tension based on ecological and economic indicators, the forest and meadow landscape zones were considered tense and conflicting, and the sub-alpine and alpine landscape zones were conditionally favorable.